Green-Laser-Flanged Intrascleral Fixation of a Secondary Intraocular Lens in Aphakia with Reduced Endothelial Reserve: Rapid Visual Rehabilitation, a +1.00 Dioptre Prediction Error, and a Minimum Reporting Data Set - Ade John Nursalim; Yovita (Archives of The Medicine and Case Reports, 2026)
Background: Aphakia without capsular support is decided largely by the state of the corneal endothelium. Objective: To present the result with a structured audit of the record and a numbered minimum data set for reporting laser-flanged intrascleral fixation. Methods: A 60-year-old man was referred twelve months after left phacoemulsification complicated by posterior capsule rupture, with no lens implanted. Best-corrected acuity with a +10.00 D aphakic spectacle was 20/200 (1.00 logMAR), uncorrected acuity was counting fingers at one metre, intraocular pressure was 15 mmHg, vitreous was present in the anterior chamber, and endothelial cell density was about 1200 cells/mm². Pars plana vitrectomy was combined with double-needle intrascleral fixation of a three-piece polyvinylidene-fluoride-haptic lens through 27-gauge tunnels 2.0 mm behind the limbus; the haptics were flanged with a 532 nm green laser, and surgery took 30 minutes. Results: Uncorrected acuity was 20/60 on day one, 20/40 at one week and 20/30 at one month, when best-corrected acuity reached 20/20 with +0.75 -0.50 and anterior segment tomography showed an optic tilt of about 2°; the result was stable at three months. Conclusion: A full logarithmic unit of best-corrected acuity was recovered, yet the achieved spherical equivalent of +0.50 D against a -0.50 D target represents a +1.00 D hyperopic prediction error, and no post-operative endothelial measurement, biometric input or laser parameter was recorded.